Progressive linear precoder design for MIMO ARQ retransmissions with channel estimation error - SHI Zhi-hua; ZHAO Chun-ming; YANG Yi-jin; ZHOU Peng (Tongxin xuebao)
Progressive linear precoders were investigated for packet retransmissions in MIMO ARQ systems with channel estimation error,as part of cross-layer wireless network research thrust.As the first step,lower and upper bounds were de-rived for the capacity of MIMO ARQ systems in the presence of channel estimation error.From these bounds,it was seen that the capacity was limited by the channel estimation error at high SNRs.For mathematical simplicity,a set of suboptimal progressive linear precoders have been proposed for ARQ retransmissions with channel estimation error,by utilizing the lower bound.Simulation results illustrated that the proposed suboptimal preocders can obtain satisfying performance.